2007
DOI: 10.1096/fj.07-8581com
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP synthase levels in brown adipose tissue are governed by the c‐Fo subunit P1 isoform

Abstract: Despite the significance of mitochondrial ATP synthase for mammalian metabolism, the regulation of the amount of ATP synthase in mammalian systems is not understood. As brown adipose tissue mitochondria contain very low amounts of ATP synthase, relative to respiratory chain components, they constitute a physiological system that allows for examination of the control of ATP synthase assembly. To examine the role of the expression of the P1-isoform of the c-Fo subunit in the biogenesis of ATP synthase, we made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 23 publications
1
53
1
Order By: Relevance
“…In contrast, ADP did not stimulate respiration in BAT mitochondria. This observation is not surprising, since BAT does not contain high amounts of ATP synthase and relies largely on glycolysis to meet ATP demands (27). Thus, despite the presence of UCP1, muscle mitochondria can still actively generate ATP.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, ADP did not stimulate respiration in BAT mitochondria. This observation is not surprising, since BAT does not contain high amounts of ATP synthase and relies largely on glycolysis to meet ATP demands (27). Thus, despite the presence of UCP1, muscle mitochondria can still actively generate ATP.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, ATP synthases from human, mouse, and bovine mitochondria also display a methionine at position 63 of subunit c, and this polymorphism on its own may account for the lack of inhibition of ATP synthase in mitochondria from these organisms. Although in humans three different isoforms of subunit c are known (13), no tissue-specific sensitivity for TMC207 can be expected, as these isoforms represent the same mature protein and differ only in the mitochondrial import sequence.…”
Section: Figmentioning
confidence: 99%
“…Recently, by using transgenic mice, this idea was proved. 114) All three isoforms of subunit c are functional, but only the P1 gene changes expression in response to cold stimulation. 112) In this report, it was shown that the expression of P1 gene is increased from the beginning of cold exposure until 24 h but that prolonged cold exposure decreases its expression.…”
Section: Time Course Of Changes In Thermogenesismentioning
confidence: 99%